Design and validation of a questionnaire to measure the attitudes of health professionals towards immigrants (AHPI) - Niewiadomska, Iwona; Jurek, Krzysztof; Dobrowolska, Beata; Deluga, Alina; Mamcarz, Izabela (Frontiers in Pharmacology, 2024)
Objective The aim of the article is to describe the validation process of a research tool used to measure the intensity and direction of medical personnel’s attitudes towards immigrant patients. Design An instrument validation design with a cross-sectional survey was conducted. The validation process was carried out in two phases. In phase 1, the content validity of the tool was analyzed. The competent judges method was used. The reliability of the judges was verified in terms of the consistency of evaluations (the I-CVI index was calculated). In phase 2, the questionnaire was tested among 340 healthcare professionals who have professional contact with immigrants, in terms of its factorial validity (exploratory and confirmatory factor analysis), internal consistency (reliability measured by Cronbach’s alpha coefficient) and absolute stability (measured by the test-retest method). Results The research results indicate satisfactory content validity of the tool (I-CVI>0.8). The reliability of the tool measured by Cronbach’s alpha coefficient was high (0.86). The reliability study based on the test - retest method (after 3 weeks) showed high consistency of measurements (0.75). Exploratory factor analysis allowed extracting 1 factor, which explains 55.7% of the variance. The validity of the one-factor solution was confirmed by confirmatory factor analysis. Satisfactory goodness of fit indices were obtained (RMSEA = 0.038; PCLOSE = 0.624; AGFI = 0.966; GFI = 0.990; CFI = 0.996). Conclusion The presented tool has satisfactory psychometric properties. The AHPI is a tool that can be used for quick assessment of the intensity and direction of attitudes of medical students and healthcare professionals towards immigrant patients, which can help shape educational and training processes.